Testing Measurement Invariance of the Schizotypal Personality Questionnaire-Brief Scores across Spanish and Swiss Adolescents - Ortuño-Sierra, Javier (Public Library of Science, 2013)
BACKGROUND: Schizotypy is a complex construct intimately related to psychosis. Empirical evidence indicates that participants with high scores on schizotypal self-report are at a heightened risk for the later development of psychotic disorders. Schizotypal experiences represent the behavioural expression of liability for psychotic disorders. Previous factorial studies have shown that schizotypy is a multidimensional construct similar to that found in patients with schizophrenia. Specifically, using the Schizotypal Personality Questionnaire-Brief (SPQ-B), the three-dimensional model has been widely replicated. However, there has been no in-depth investigation of whether the dimensional structure underlying the SPQ-B scores is invariant across countries. METHODS: The main goal of this study was to examine the measurement invariance of the SPQ-B scores across Spanish and Swiss adolescents. The final sample was made up of 261 Spanish participants (51.7% men; M = 16.04 years) and 241 Swiss participants (52.3% men; M = 15.94 years). RESULTS: The results indicated that Raine et al.'s three-factor model presented adequate goodness-of-fit indices. Moreover, the results supported the measurement invariance (configural and partial strong invariance) of the SPQ-B scores across the two samples. Spanish participants scored higher on Interpersonal dimension than Swiss when latent means were compared. DISCUSSION: The study of measurement equivalence across countries provides preliminary evidence for the Raine et al.'s three-factor model and of the cross-cultural validity of the SPQ-B scores in adolescent population. Future studies should continue to examine the measurement invariance of the schizotypy and psychosis-risk syndromes across cultures.